ANALISIS STRUKTURAL DAN KEARIFAN LOKAL DALAM FABEL ETNIS PAK-PAK SALING MENGENAL DAN BERSAHABAT SERTA RELEVANSINYA TERHADAP PEMBELAJARAN BAHASA INDONESIA - Chairun Nisa (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2024)
The purpose of this study is to study the structure and explain the value of local wisdom contained in the ethnic pak-pak fable entitled know each other and be friends by Farizal. The values obtained can later be developed into teaching materials for junior high school students according to the syllabus used by the teacher. The method used in this study uses a library approach. The sources of data used in this research are journals, books, and internet sites related to the topics that have been selected. The data analysis technique used in this research is the content analysis method. The results of this study show that the Pak-Pak community has long had positive values such as humility, friendliness and sociability, leadership, mutual cooperation, social solidarity, decency and harmony. This is reflected in the oral/regional literary tradition that is owned, namely fables. The values of advice/advice contained in the ethnic pack fables that have been analyzed can be used as teaching materials, so that they have relevance as literature learning materials.